A Program To Generalize Contour Lines - Abdul Rahman, Alias (Fakulti Ukur dan Harta Tanah, 1994)
This paper describes a digitized points reduction algorithm, and reviews a number of existing algorithms. A complete computer program based on the developed algorithm is presented.